1999
DOI: 10.1023/a:1018702323648
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: While first-wave Vietnamese immigrants adapted well to life in the United States, subsequent immigrants have had greater adjustment difficulties, including more evidence of psychological distress. This study aimed to analyze psychosocial adaptation differences among three generations of recent Vietnamese immigrants, as well as to examine predictors of mental distress in the sample as a whole. A community sample of 184 recent Vietnamese immigrants, categorized as either elderly, middle-aged, or young adults, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Research conducted in the UK (Rex & Tomlinson, 1979) found that first-generation Asian migrants use the separation strategy of adaptation to avoid contact with British people because of the language barrier and differences in family values, religion and lifestyle. As a result of their lack of acculturation, first-generation immigrants also experience more stress than subsequent generations (Shapiro et al, 1999). While younger generations have a tendency to acculturate with far less difficulty than adults, this can contribute to the dilemma that causes conflict within the family.…”
mentioning
confidence: 99%
“…Research conducted in the UK (Rex & Tomlinson, 1979) found that first-generation Asian migrants use the separation strategy of adaptation to avoid contact with British people because of the language barrier and differences in family values, religion and lifestyle. As a result of their lack of acculturation, first-generation immigrants also experience more stress than subsequent generations (Shapiro et al, 1999). While younger generations have a tendency to acculturate with far less difficulty than adults, this can contribute to the dilemma that causes conflict within the family.…”
mentioning
confidence: 99%
“…Acculturation is inconsistently associated with psychological distress among Asian Americans. The majority of the studies document that level of acculturation has an inverse association with psychological distress among various Asian American groups (Beiser, 1988;Padilla, Wagatsuma, & Lindholm, 1985;Shapiro et al, 1999;Sue, Sue, Sue, & Takeuchi, 1995;Westermeyer, Neider, & Vang, 1984). Others have presented different results.…”
mentioning
confidence: 99%